2005
DOI: 10.1196/annals.1349.005
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin Regulates Differentiation of Rhesus Monkey Embryonic Stem Cells to Hematopoietic Cells

Abstract: Thrombopoietin (TPO) is the primary regulator of megakaryocyte and platelet production in vitro and in vivo. It supports also survival and proliferation of hematopoietic stem cells. The TPO receptor, c-mpl, is a member of the protooncogene family. Our studies focused on the effect of TPO on proliferation and differentiation of rhesus monkey embryonic stem cells to hematopoietic cells. The rationale of the present investigations was the finding that patients with congenital amegakaryocytic thrombocytopenia (CAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Thus, it appears that in human EB‐derived cultures, signaling through TPO receptor (c‐mpl) activates signaling pathways involved in early hematopoiesis and that VEGF enhances this mechanism. This process was independent of BMP4, which has been shown in other reports to effectively enhance human ES‐derived hematopoiesis [17], but correlated with a recent report on nonhuman primate ES cells in which TPO and VEGF induced early erythroid differentiation [16].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Thus, it appears that in human EB‐derived cultures, signaling through TPO receptor (c‐mpl) activates signaling pathways involved in early hematopoiesis and that VEGF enhances this mechanism. This process was independent of BMP4, which has been shown in other reports to effectively enhance human ES‐derived hematopoiesis [17], but correlated with a recent report on nonhuman primate ES cells in which TPO and VEGF induced early erythroid differentiation [16].…”
Section: Resultssupporting
confidence: 82%
“…Previous studies have shown that hematopoietic differentiation of human ES cells using the EB differentiation model requires bone morphogenic protein (BMP4) in combination with a few other cytokines, such as stem cell factor (SCF), Flt3 ligand (Flt3L), IL‐3, IL‐6, and granulocyte macrophage‐colony stimulating factor [14, 15]. However, a recent report demonstrated that TPO regulates proliferation and differentiation of rhesus EBs to hematopoietic and endothelial progenitors without BMP4 but instead required VEGF, SCF, and Flt3L [16]. TPO alone was not able to stimulate formation of hematopoietic and endothelial progenitors, whereas the addition of VEGF enhanced their generation.…”
Section: Introductionmentioning
confidence: 99%
“…TPO also controls the expression levels and modifies the function of the homeodomain proteins HOXB4 and HOXA9 . Recently, we found that TPO in combination with VEGF promotes hematopoietic differentiation of rhesus monkey ES cells, which was later confirmed in a human system …”
Section: Introductionmentioning
confidence: 78%
“…15 TPO also controls the expression levels and modifies the function of the homeodomain proteins HOXB4 and HOXA9. 16,17 Recently, we found that TPO in combination with VEGF promotes hematopoietic differentiation of rhesus monkey ES cells, 18 which was later confirmed in a human system. 19 Bone morphogenetic protein 4 (BMP4) is a morphogenetic signaling molecule essential for embryonic ventral mesoderm patterning and formation of hematopoietic precursor cells during embryogenesis and in the postnatal period.…”
Section: Introductionmentioning
confidence: 88%
“…TPO acts as a lineage-specific hematopoietic growth factor and exerts effects on early hematopoietic stem cells [38]. Prior studies have demonstrated that addition of TPO increases formation of primitive hematopoietic progenitors in primate EB differentiation models [39]. It was also shown that TPO and VEGF induce early hematopoietic differentiation of EB-derived human ES cells [40].…”
Section: Discussionmentioning
confidence: 99%